Characterization of rainstorm modes along the upper mainstream of Yangtze River during 2003–2016. (16th October 2017) - Wu, Xushu; Guo, Shenglian; Liu, Dedi; Hong, Xingjun; Liu, Zhangjun; Liu, Pan; Chen, Hua
ABSTRACT: Accurate knowledge of extrveme rainfall mode (time distribution) is crucial for many fields, such as hydraulic structure design, flood control and reservoir operation. The rainstorm modes along the upper mainstream of Yangtze River (UMYR) during 2003–2016 were investigated by fuzzy mode identification method, linear regression and Mann–Kendall test. Results show that unimodal rainstorms are more frequently seen than bimodal ones, and those with late peaks are dominant along UMYR. Moreover, rainstorms tend to centre on downstream UMYR. Trend analysis reveals moderate decreases in regional mean rainstorm frequency and amount, but an increase in regional mean peak intensity. Unimodal rainstorms with early peaks and bimodal rainstorms with early and late peaks have increased significantly. However, unimodal rainstorms with late peaks and bimodal rainstorms with middle and late peaks show decreases. Spatially, decreases in rainstorm frequency, amount and peak intensity are found in downstream, while peak intensity shows an increasing trend in the upper UMYR. Along the river reach, mean rainstorm levels are generally below 100 mm. In comparison to bimodal rainstorms, unimodal rainstorms are more intense, and those with middle peaks are considered most intense with mean levels of peak intensity generally ranging from 25 to 50 mm h −1 . For other rainstorm modes, the mean levels of peak intensity are generally below 25 mm h −1 . Finally, we found there is a potential change in the dominant rainstorm mode in downstream UMYR, where unimodal rainstorms with early peaks have become the prevalent local rainstorm mode in recent years, replacing unimodal rainstorms with late peaks. Abstract : Locations of the study region and the 76 rain gauge stations used in this study.